On physical remodeling and institution strengthening: an evaluation of the implications of the pilot field channel experience for the rehabilitation project at Uda Walawe, Sri Lanka - Merrey, Douglas J.; Jinapala, K. (International Water Management Institute, 1988)
This paper is a substantially revised version of a draft paper previously circulated to some officials in Sri Lanka. The title of that paper was "Testing a New Field Channel Design: A Pilot Project of the Uda Walawe Rehabilitation Project, Sri Lanka. It was reviewed by the International Irrigation Management Institute (IIMI) - Sri Lanka Consultative" Consultative Committee at its January 1988 meeting; as the minutes of that meeting indicate, the Committee members recognized- the significance of the main findings of the draft report, and agreed that physical rehabilitation by itself could be counter productive unless supported by proper institutional changes. The paper is based on periodic observations (approximately weekly) of farmers' use of a rehabilitated pilot field channel (FC), and interviews with both farmers and field level officials, over two seasons in the Uda Walawe Scheme, Sri Lanka.